Prevalence of QT prolongation and associated LVEF changes in diabetic patients over a four-year retrospective time period - Zhongju Lu; Lloyd Lense; Mohit Sharma; Ankit Shah; Ying Luu; Lucien Cardinal; Joan Faro; Alan Kaell (Journal of Community Hospital Internal Medicine Perspectives, 2017)
Aim: To evaluate the prevalence and longitudinal changes of prolonged QTc in DM patients admitted to our community hospital, and to determine, if any, its correlation with changes of left ventricular ejection fraction (LVEF). Methods: A retrospective chart review of patients with Type 1 (T1DM) and Type 2 (T2DM) with at least two admissions during a four-year period was performed to identify QTc interval, and LVEF, as measured on transthoracic echocardiogram. Changes in QTc and LVEF between patient hospital admissions were compared. Results: A prolonged QTc interval was found in 66.7% (n = 24) of type 1 and 51.3% (n = 154) type 2 diabetic patients. The QTc interval is progressively increased in both type 1 and type 2 diabetes during follow-up, although it did not reach statistical significance. A total of 62% patients (23 out 37 patients) had a reduction of LVEF during follow-up. Conclusion and Discussion: High prevalence of QTc prolongation was confirmed in hospitalized patients with in both T1DM and T2DM. Significant reduction of LVEF correlated with QTc prolongation over a mean of 17.3 months in T2DM patients, and may have implications for interventions. Abbreviations CHF: Congestive heart failure LVEF: Left ventricular ejection fraction